Global uniqueness in a passive inverse problem of helioseismology. (24th April 2020) - Agaltsov, A D; Hohage, T; Novikov, R G
Abstract: We consider the inverse problem of recovering the spherically symmetric sound speed, density and attenuation in the Sun from the observations of the acoustic field randomly excited by turbulent convection. We show that observations at two heights above the photosphere and at two frequencies above the acoustic cutoff frequency uniquely determine the solar parameters. We also present numerical simulations which confirm this theoretical result.